Differing trends in the incidence of vascular comorbidity in MS and the general population. Issue 2 (April 2016) - Marrie, Ruth Ann; Fisk, John; Tremlett, Helen; Wolfson, Christina; Warren, Sharon; Blanchard, James; Patten, Scott B.
Abstract: Background: Although the adverse effects of vascular comorbidities are increasingly recognized in multiple sclerosis (MS), the epidemiology of these conditions remains poorly understood. Methods: Using population-based administrative data, we identified 44, 452 Canadians with MS and 220, 849 age-, sex- and geographically matched controls. We applied validated definitions to estimate the incidence of diabetes, hypertension, hyperlipidemia, and ischemic heart disease (IHD) from 1995 to 2005. Results: Of the MS cases, 31, 757 (71.4%) were in female participants, with a mean (SD) age at the index date of 43.8 (13.7) years. Over time, the age-standardized incidence of diabetes rose more in the MS population (incidence rate ratio [IRR] per year 1.06; 95% confidence interval [CI] 1.03–1.08) than in the matched population (IRR per year 1.02; 95% CI 1.01–1.03). Temporal trends in the age-standardized incidence of hyperlipidemia, hypertension, and IHD were similar in both populations. Among those aged 20–44 years, the incidence of IHD was higher in the MS population (IRR 1.59; 95% CI 1.19–2.11). The increased incidence of IHD in the MS population was attenuated among those aged 60 years and older (IRR 1.01; 95% CI 0.97–1.06). Conclusions: The incidence rates of diabetes, hypertension, and hyperlipidemia are rising within the MS population. Programs to systematically prevent and treat these conditions are needed.